A randomized controlled trial of a resilience-based intervention for children affected by parental HIV: Educational outcomes at 24-, 30-, and 36-months. (April 2018) - Harrison, Sayward E.; Li, Xiaoming; Zhang, JiaJia; Zhao, Junfeng; Zhao, Guoxiang
Children of parents with human immunodeficiency virus (HIV) are at-risk for a variety of negative outcomes, including poor educational achievement. The multi-level, resilience-based ChildCARE intervention has been found to yield short-term improvement in a number of school-related variables for children affected by parental HIV. However, no studies have examined whether educational gains persist. Thus, this study evaluated whether children who received the ChildCARE intervention displayed better educational outcomes than children assigned to a control group at 24-, 30-, and 36-months post-intervention. We enrolled 790 Chinese children affected by parental HIV in a four-arm randomized controlled trial to evaluate the intervention components of ChildCARE . Children and their caregivers were randomized to a control group, child-only intervention, child + caregiver intervention, or child + caregiver + community intervention. School outcomes at 24-, 30-, and 36-months suggested limited support for the efficacy of the intervention to yield sustained improvements in educational outcomes. Findings highlight the need for comprehensive and coordinated efforts that involve caregivers, communities, and schools to support children made vulnerable by parental HIV in China and around the world.